Genetic variation underlies the plastic response to shade of snapdragon plants (Antirrhinum majus L.). Issue 2 (3rd April 2021) - Mousset, Mathilde; Marin, Sara; Archambeau, Juliette; Blot, Christel; Bonhomme, Vincent; Garaud, Laura; Pujol, Benoit
ABSTRACT: A classic example of phenotypic plasticity in plants is the set of traits that change in response to shade. There is widespread evidence that plants in low light conditions often avoid shade by growing taller or by increasing their photosynthetic efficiency, i.e. the shade avoidance syndrome. Whether this plasticity might evolve in response to natural selection depends upon the presence of its standing genetic variation in wild populations. There is limited evidence for heritable standing variation in the plastic response of plants to shade. In this study, we used an experimental common garden approach to investigate this plastic response in snapdragon plants ( Antirrhinum majus L.) originating from four natural populations from the Mediterranean region. Our results showed that individual plants reacted strongly to the presence of shade by growing longer shoots, longer internodes, and increasing their specific leaf area in these four populations. Our results also revealed genetic variation for the plastic response within these populations, as well as little genetic constraints to its evolution. Our findings imply that natural populations of A. majus harbour standing genetic variation for phenotypic plasticity in response to shade, providing them the potential to evolve in response to selection.